No‐tillage and nitrogen fertilization on soil chemical properties under dryland wheat–sorghum–fallow rotation - Augustine K. Obour; Johnathon D. Holman; Logan M. Simon; Yared Assefa (Agrosystems, Geosciences & Environment, 2023)
Abstract The main objective of the present study was to investigate changes in soil organic carbon (SOC), pH, as well as macro‐ and micronutrient concentrations in the top 0‐to‐5‐ and 5‐to‐15‐cm soil depths under no‐tillage (NT) and conventional tillage (CT) practices at different nitrogen (N) application rates. The soil analysis was conducted in 2019 and 2020 from CT and NT treatments from a long‐term study conducted near Hays, KS, with N fertilizer rates of 0, 45, 90, and 134 kg N ha−1. Averaged across years, SOC in the top 0‐to‐5‐cm soil depth under NT was 19% greater than that measured in CT, but SOC was not different between the two tillage practices in the 5‐to‐15‐cm depth. The SOC concentration increased by 24–25% within the top 0‐to‐5‐cm soil depth with increasing N rate from 0 to 90 or 134 kg N ha−1. Soil pH declined at rates of 0.004 and 0.007 for every kg ha−1 increase in N rate for CT and NT treatments within the 0‐to‐5‐cm soil depth. Nitrate‐N concentration under NT at the top 0–5 cm soil was 55% more than CT but ammonium‐N concentration was unaffected by tillage or N rate. Phosphorus (P), zinc (Zn), and iron (Fe) concentrations measured in the top 0–5 cm were 24, 34, and 33% greater in soils under NT compared with CT, respectively. Findings of the study suggest pH and SOC stratification in long‐term NT systems can affect soil macro‐ and micronutrient concentrations and availability in dryland crop production systems.